2013
DOI: 10.1074/jbc.m113.458141
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor (EGF)-induced Corneal Epithelial Wound Healing through Nuclear Factor κB Subtype-regulated CCCTC Binding Factor (CTCF) Activation

Abstract: Background:We study NF-B-activated CTCF in EGF-induced wound healing. Results: Corneal epithelial wound healing was significantly impaired because of the lack of CTCF activity in NFB-p50 Ϫ/Ϫ mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…In contrast, GO enrichment analysis of the EGF-upregulated genes showed that they were significantly enriched in immune response, response to wounding, and defense response (Table 2). This is concordant with previous reports showing that EGF stimulates CECs during wound healing 13–15, 17 . Our functional analysis indicates that K+Y medium should be suitable for effective ex vivo proliferation of LECs.
Figure 3Volcano plot of statistical significance against log 2 fold-change between EGF-treated LECs and K+Y-treated LECs.
…”
Section: Resultssupporting
confidence: 94%
“…In contrast, GO enrichment analysis of the EGF-upregulated genes showed that they were significantly enriched in immune response, response to wounding, and defense response (Table 2). This is concordant with previous reports showing that EGF stimulates CECs during wound healing 13–15, 17 . Our functional analysis indicates that K+Y medium should be suitable for effective ex vivo proliferation of LECs.
Figure 3Volcano plot of statistical significance against log 2 fold-change between EGF-treated LECs and K+Y-treated LECs.
…”
Section: Resultssupporting
confidence: 94%
“…A), both of which have been shown to promote the production of epithelial cells (Singh and Foster, ; Yano et al, ; Qiao et al, ; Richardson et al, ; Wang et al, ; Wong and Rossant, ; Peterson et al, ). For example, EGF plays an important role during the corneal wound healing process by improving epithelial proliferation(Wang et al, ), while KGF markedly influences epithelial growth and differentiation during lung morphogenesis (Shiratori et al, ). The immunofluorescence staining and western blotting results indicated that EGF was able to efficiently induce the expression of CRYAA in the monolayer cells with homogenous morphology (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling activates an NF-κB pathway, which leads to transcriptional repressor CTCF activation and PAX6 downregulation (Li and Lu, 2005; Lu et al, 2010; Wang et al, 2012a) resulting in cell migration and proliferation in corneal epithelial cells (Imanishi et al, 2000). Recent studies (Wang et al, 2013) have demonstrated that in NF-κB p50 knockout mice, corneal epithelial wound healing is significantly delayed, suggesting that NF-κB signaling pathways play important roles in growth factor-promoted corneal epithelial self-renewal and wound healing. EGFR signaling also activates histone deacetylase 6 (HDAC6), which deacetylates α-tubulin, and promotes corneal epithelial cell migration and healing of debridement wounds.…”
Section: Corneal Epithelial Wound Healingmentioning
confidence: 99%